THE ROLE OF ADMINISTRATIVE ADAPTATION IN HUMAN RESOURCE MANAGEMENT IN ENHANCING JOB SATISFACTION WITHIN EDUCATIONAL INSTITUTIONS (World Economics and Finance Bulletin, 2026)
This paper examines the role of human resource-focused administrative adaptation in influencing job satisfaction within academic environments, considering such adaptability as a contributing factor to operational performance and workforce stability. Using statistical modeling via SPSS and AMOS (version 27), the study tested a series of hypotheses to explore the direct effects between the selected variables. Data collection involved distributing a structured questionnaire to a random sample of employees from five colleges, aiming to provide a quantitative perspective on how administrative agility relates to overall job satisfaction levels . The research was organized into four main components: the scientific methodology, the theoretical foundation, the practical analysis, and finally, the conclusions with recommendations. The findings revealed a statistically significant positive association between administrative adaptability in human resource management and employees’ job satisfaction. While the correlation was evident, the results suggest that administrative flexibility functions as one of several factors that may contribute to enhancing stability and efficiency across academic work environments.